2019
DOI: 10.1155/2019/5125923
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Dynamic Impact Mechanical Characteristics of Prestressed Saturated Fractured Coal and Rock

Abstract: e natural and water-saturated states of coal samples under static and static-dynamic loads were tested using the Split-Hopkinson pressure bar (SHPB) method and RMT-150 system, respectively. e differences in the strength reduction coefficient and elastic modulus reduction coefficient of water-saturated coal samples under static and static-dynamic loads were discussed. e experimental results for coal were compared with the corresponding characteristics of typical sandstone samples under static and static-dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Under coupled static and dynamic loads, in the process of applying axial static preload, a certain amount of elastic strain energy had been deposited inside the limestone specimen, which should be considered in the calculation method [37,38].…”
Section: Energy Dissipation Analysis Of Limestonementioning
confidence: 99%
“…Under coupled static and dynamic loads, in the process of applying axial static preload, a certain amount of elastic strain energy had been deposited inside the limestone specimen, which should be considered in the calculation method [37,38].…”
Section: Energy Dissipation Analysis Of Limestonementioning
confidence: 99%
“…erefore, the influence of water content on the mechanical properties of coal under complex stress conditions cannot be ignored. Wang et al [29] found that the strengths of coal specimens saturated for seven days are 52% lower than those of natural coal specimens. Gu et al [30] proposed a constitutive model considering the damage by water to describe the deformation of coal.…”
Section: Introductionmentioning
confidence: 99%
“…Massive efforts have been made to explore the effect of water on the mechanical properties of coal [17][18][19][20][21][22][23][24][25][26]. For example, White and Mazurkiewicz [17] conducted uniaxial compressive tests on Nemo coal specimens with different water contents.…”
Section: Introductionmentioning
confidence: 99%